2005
DOI: 10.3758/bf03193079
|View full text |Cite
|
Sign up to set email alerts
|

Is memory for stimulus magnitude Bayesian?

Abstract: This study was designed to determine whether memory for stimulus values is a Bayesian weighting of the magnitude of a stimulus and the central tendency of an exemplar's category (Huttenlocher, Hedges, & Vevea, 2000). In five experiments, participants reproduced the remembered size of a geometric figure drawn from one of two categories whose means for size differed. Reproductions were biased toward the mean of the combined distribution rather than the mean of either category. Reproductions were also influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Many studies have examined the effects of category membership on stimulus reproduction by using a serial reproduction task in which participants briefly viewed an object and then immediately estimated one of its attributes (e.g., the length of lines, size of shapes, or brightness of gray squares) from memory (e.g., Huttenlocher, Hedges, & Vevea, 2000;Sailor & Antoine, 2005). However, whether the categorical information of objects affects stimulus reproduction remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effects of category membership on stimulus reproduction by using a serial reproduction task in which participants briefly viewed an object and then immediately estimated one of its attributes (e.g., the length of lines, size of shapes, or brightness of gray squares) from memory (e.g., Huttenlocher, Hedges, & Vevea, 2000;Sailor & Antoine, 2005). However, whether the categorical information of objects affects stimulus reproduction remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, Sailor and Antoine provided further evidence of a central-tendency bias for single item memory but also suggested that the bias could be explained through the influence of immediately preceding stimuli; if a stimulus from one end of a distribution is presented, the preceding stimulus is more likely to be a less extreme value. Sailor and Antoine (2005) showed that such sequential dependencies could produce a central-tendency bias. However, Duffy, Huttenlocher, Hedges, and Crawford (2010) directly tested this hypothesis against the central-tendency bias view; they reported two experiments that showed that participants adjust their estimates towards the mean of all the stimuli encountered previously rather than towards a smaller and more recently encountered subset.…”
mentioning
confidence: 99%
“…They note that these findings do not mean that there is never an influence of recent, prior stimuli; rather, their results imply that such an influence is generally far smaller than the influence of the entire distribution. Sailor and Antoine (2005), as well as DeCarlo and Cross (1990), reported evidence to the effect that both the distribution as a whole and the immediately preceding stimulus affected estimates, but the influence of the immediately preceding stimulus was minor, relative to the influence of the entire distribution. In summary, there is no strong evidence for an explanation of the central tendency bias as a memory distortion caused by a subset of immediately preceding stimuli.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that stimulus history biases perceptual judgments is well-known. Broadly speaking, it appears in two ways-biases to (or away from) the mean of a stimulus distribution (1)(2)(3)(4)(5)(6)(7)(8)(9), referred to as central-tendency biases, and biases to (or away from) recently observed stimuli (10)(11)(12)(13)(14)(15)(16), referred to as n − 1 biases.…”
mentioning
confidence: 99%